USE OF GEOINFORMATION TECHNOLOGIES FOR THE ESTIMATE OF SPATIAL HETEROGENEITY OF ARABLE SOIL MOISTURE - АЧАСОВ, А. Б.; АЧАСОВА, А. О.; СЕЛІВЕРСТОВ, О. Ю.; СЄДОВ, А. О.; ТОВСТОКОРИЙ, О. В. (Man and Environment. Issues of Neoecology, 1970)
The possibility of geoinformation terrain analysis using for the purpose of spatial estimation of soil moisture is shown. The analysis of the individual parameters of the relief affecting the spatial heterogeneity of topsoil moisture. It is proved that the coefficient of xeromorphic most suitable for the prediction of automorphic soil moisture.